2021
DOI: 10.1021/acssuschemeng.1c02682
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Aromatics to PHA Polymers: Nitrogen and Oxygen Are the Key Factors for Pseudomonas

Abstract: Many wild type Pseudomonas strains have the potential to contribute to the valorization of lignin in future biorefineries. Through a robust aromatic catabolism, i.e., biofunneling capacity, they can ease the inherent aromatic heterogeneity found in lignin hydrolysates and accumulate naturally marketable biopolymers like mcl-polyhydroxyalkanoate (mcl-PHA) under nitrogen limitation. Besides a comparative strain evaluation, we present fundamental research on the funneling of aromatic mixtures under specific biopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 60 publications
2
7
1
Order By: Relevance
“…A highly viscous medium may adversely affect the dissolution and diffusion of oxygen, hindering lignin metabolism and PHA synthesis ( Liu et al, 2018 ). In addition, aromatic derivatives possessing aldehyde and methoxy groups may enhance the inhibitory effects on the P. putida cells and lead to poor PHA accumulation ( Shin et al, 2019 ; Ramirez-Morales et al, 2021 ). Furthermore, the salt concentration in APL from alkaline fractionation was increased and could be harmful to cell growth and PHA accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…A highly viscous medium may adversely affect the dissolution and diffusion of oxygen, hindering lignin metabolism and PHA synthesis ( Liu et al, 2018 ). In addition, aromatic derivatives possessing aldehyde and methoxy groups may enhance the inhibitory effects on the P. putida cells and lead to poor PHA accumulation ( Shin et al, 2019 ; Ramirez-Morales et al, 2021 ). Furthermore, the salt concentration in APL from alkaline fractionation was increased and could be harmful to cell growth and PHA accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…However, lignocellulosic biorefineries have traditionally exploited the carbohydrates fraction to generate biofuels and chemicals, while the valued lignin fraction has remained as underutilized waste . Recently, advances in synthetic biology and metabolic engineering biological valorization of lignin has become possible, as, in some microorganisms, metabolic pathways have been constructed for the conversion of heterogeneous phenolics via biological funneling to value-added products such as PHAs. , Utilizing lignocellulose may become a promising, greener, economic, and sustainable approach to PHA production (Table ), as resources are not in direct competition with food values. , …”
Section: Closed-loop Biomass-based Biorefinery Conceptmentioning
confidence: 99%
“…showing the effects of C:N ratio on stimulating PHA synthesis. 20,22 However, further increase in feed volume could better enhance PHA accumulation than further increase in C:N ratio as shown in the effect of the quadratic (Q) term for both factors. This suggested that a very high C:N ratio may not increase the production of PHA, potentially due to the negative effect inserting on cell growth.…”
Section: Fed-batch Optimization With Doementioning
confidence: 99%
“…19 Recently, a milestone of PHA development from lignin has been accomplished through the optimization of bioprocess. 20 Effects of C:N ratio and aeration on mcl-PHA production were examined leading to high PHA titer (approximated 0.5 g/L) from lignin through batch process optimization. Enhanced lignin to PHA conversion would be very likely if fedbatch strategy was further implemented in process optimization.…”
mentioning
confidence: 99%